Distribuição espacial e temporal de bactérias heterotróficas bênticas em ambientes da planície de inundação do alto rio Paraná. - Santana, Natália Fernanda (2011)
In river floodplain systems, spatial and temporal fluctuations of limnological characteristics and attributes of communities are controlled by the frequency, intensity and duration of flood pulse. Furthermore, the increasing in water level provides an improve of similarity between different environments and increases the levels of nutrients by leaching from coastal area and decomposition of aquatic macrophytes. This organic matter tends to be settled in the sediment, where can occur biogeochemical processes associated with microorganisms. The vertical distribution of bacterial density in floodplain lakes in sediment layers were characterized for the Upper Paraná River and its relationship to physical and chemical characteristics of sediment. Also was checked the similarity between the environments, spatiotemporal changes of levels of total Kjeldahl nitrogen, total phosphorus, bacterial density and biomass in initial layers of sediment, its variability over hydrological cycle, and investigate the relationship between water level and de variables analyzed. The results showed a gradient of vertical distribution in bacterial density, with predominantly coccoid. The analysis of variance applied to test differences between the environments over time showed that there was no temporal variation, only spatial differences, highlighting the wide variability of habitat conditions and therefore present in these systems. Correlations were used to evaluate the influence of water level in the nutrient concentrations and bacterial biomass, but the data indicated a weak correlation, possibly due to the time period has not presented remarkable flood, which would allow the leaching of floodplain causing changes in biotic and abiotic variables. Trend was also observed accumulation of total phosphorus and inorganic material in the sediment.